Efficacy of Cognitive Behavior Therapy, Pelvic Floor Therapy, Integrated Therapy, and Pharmacotherapy in the Treatment of Chronic Pelvic Pain in Women: A Randomized Controlled Trial - Bushra Akram; Ahmad Bilal (Pakistan Journal of Medical Sciences, 2026)
Objective: The objective of the current study was to determine the efficacy of Cognitive Behavior Therapy (CBT-cp), Pelvic Floor Therapy (PFT), Integrated Therapy (Combination of CBT-cp and PFT), and Pharmacotherapy in the Treatment of Chronic Pelvic Pain in women, compared with the placebo group. Methodology: A five-arm (four intervention arms and one placebo arm), Randomized Controlled Trial (RCT) was conducted, to examine the effectiveness of CBT-cp, PFT, and Pharmacotherapy in the treatment of Chronic Pelvic Pain in women, compared with the placebo group. The sample comprised 175 female patients with CPP; 141 patients completed the study. They were presented to the Outpatient Department of the Department of Obstetrics & Gynecology, and the Department of Physiotherapy at Nishtar Hospital, Multan, Pakistan, from April to June, 2025. The Impact of Female Chronic Pelvic Pain Questionnaire (IF-CPPQ), Urdu version was used as primary outcome measure. The intervention lasted three months. Results: Results showed that the mean CPP scores significantly decreased at the Posttest (p < 0.001) on IF-CPPQ, although they did not maintain at follow-up. It demonstrated that posttest and follow-up scores were significantly different from pretest scores in all the intervention groups. The Integrated therapy group differed considerably from the CBT-cp, PFT, Pharmacotherapy, and Placebo groups in CPP reduction. Conclusion: The Integrated therapy is the most effective and statistically significant in reducing CPP compared with CBT-cp, PFT, Pharmacotherapy, and Placebo.